PENGARUH MOTIVASI DAN KEMAMPUAN TERHADAP KINERJA KARYAWAN (Studi Empiris di Rumah Sakit Umum Daerah Kabupaten Kepahiang) - Pesi Susanti; Khairul Bahrun; Merta Kusuma ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2020)
This study entitled the effect of motivation and ability on employee performance (Empirical Study in Kepahiang Regency General Hospital). Human resources constitute resources that have advantages compared to other resources related to organizations within the company. Hospital organizations are complext and unique organizations. Said to be complex because of many complicated problems. In achieving company goals, surely competent human resources are needed and have good performance in order to support the company's success. This study aimed at determining the effect of motivation and ability on employee performance (Empirical Study in Kepahiang Regency General Hospital). The study employed a quantitative descriptive method with a total sample of 125 samples. Then, the study applied multiple linear regression analysis technique to analyze data with hypothesis test. With the results of this study, motivation affected the performance of Kepahiang Regency General Hospital Employees. This case is proven by t-test showing a value of t count of 5,569 then t count > t table (5,569> 1.9796) and (sig <Î± = 0,000 <0.050), it states that there is a significant influence, ability (X_2), namely t_count>t_table (11.693> 1.9796) and (sig <Î± = 0.000 <0.050), it states that there is a significant influence, Employee Performance (Y) F_count of 211.926 with F_table value of 1.7992 namely (211.926> 1.7992) and (sig aÌ = 0.000 <0.050). Further, it can be concluded that H_3 is accepted meaning that simultaneously variables motivation and ability have a significant effect on employee performance at the Kepahiang Regency General Hospital. Keywords: Motivation, Ability, Employee Performance